Bersaing dengan google: Bagaimana perpustakaan tetap unggul dalam pencarian informasi - Parhan Hidayat (Pusat Perpustakaan UIN Syarif Hidayatullah Jakarta, 2015)
The existence of Google as a popular search engines has significant effect on the view of some people about the function of library. They assume that a library function has been shifted by the presence of google. This paper tries to discuss that google versatile presence does not automatically rule out the function of a library as a service provider with accurate information. The library has several advantages that are not owned by google. First, all the collections usually pass through a rigorous selection process by the selection team. This is different to google which is procuring information through a machine called spiders or web crawlers. Secondly, with the number of hybrid library, with Google itself has become a part of the hybrid library tool itself. Third, the library will also provide a more humane service to the existence of a librarian. Professional librarians capable of providing relevant and accurate information to the information seekers.